Folkcomunicação na imprensa de referência : um sentido popular da copa do mundo de 2014 no Jornal Zero Hora - Martins, Marcel Neves (2017)
This thesis examines the construction of a popular sense of the 2014 World Cup, in Brazil, by the Zero Hora newspaper, from Porto Alegre, Rio Grande do Sul‟s capital. The study overall objective is realize how Zero Hora built a popular sense for the mega-sports event, through folkcommunication in their texts, during the course of the competition in Brazil, from June 12 to July 13, 2014. Laurence Bardin‟s “content analysis” was adopted as research method to investigate the special section of Zero Hora, created to cover and thematize the World Cup, “Jornal da Copa”, with daily circulation in the editions of ZH, from June 12 to July 14, 2014. The presented analysis resulted from exploring about 300 texts between news, articles and stories. The subjects were divided into six thematic areas – “games”, “people”, “Porto Alegre”, “protagonists”, “Brazilian Soccer Team” and “police” –, that guided the examination of Zero Hora‟s communication strategies for the 2014 World Cup. The working hyphotesis, validated by the analysis, is that Zero Hora, as reference press, practiced a popular journalism, through a folkcommunication process. The research pointed that the popular sense of the 2014 World Cup intended by Zero Hora was the integration between the press and the event and the press with the newspaper‟s readers, manly with the sports sections readers and soccer supporters, potential competition audience. Zero Hora sought to promote the integration of the local community as a whole to the mega-sports event by the engagement of its journalists in media coverage of the 2014 World Cup. The analysis shows the attempt of a society mental union. Our research is based on Luiz Beltrão (1918- 1986) folkcommunication paradigm, positioning itself in the folkmídia studies that explores the popular culture appropriation processes by the mass media.